2005
DOI: 10.1002/jsfa.2407
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide residues in poultry feed, chicken muscle and eggs at a poultry farm in Punjab, India

Abstract: Animals intended for human food may absorb pesticides from residues in their feed, water or during direct/indirect exposure in the course of pest control. The objective of the present investigation was to monitor organochlorine pesticide residues in poultry feed, chicken muscle and eggs at a selected poultry farm. The samples were Soxhlet extracted for 8 h in 200 mL hexane-acetone (1:1, v/v) mixture. The clean-up of the samples was performed by silica gel column chromatography and analysis was done on a gas ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 7 publications
1
33
2
Order By: Relevance
“…These animals have free range on the property including access to the DDT exposed floors inside the sprayed homesteads. DDT has been shown to accumulate in a number of chicken tissues including fat (Vazquez-Moreno et al, 1999), muscle (Aulakh et al, 2005) and liver (Tao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…These animals have free range on the property including access to the DDT exposed floors inside the sprayed homesteads. DDT has been shown to accumulate in a number of chicken tissues including fat (Vazquez-Moreno et al, 1999), muscle (Aulakh et al, 2005) and liver (Tao et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A residue level of 0.007 ppm and 0.045 ppm was reported by Panseri [12] and Deka [13] in fodder samples, which is far below the specified MRL value by EU (CE: 698: 2005) is 0.1 ppm, whereas higher levels (0.42 ppm) was reported by Aulakh [14] for endosulphan sulfate. Residual concentration of 0.001 ppm and 0.02 ppm were reported by Panseri [12] and Aulakh [14] respectively in the fodder samples, which are far below the MRL value (0.01 ppm) specified by EU (CE:398: 2005) in fodder for heptachlor. Fagnani et al [15] reported the residual concentration of dimethoate in fodder sample as 0.01 μgl −1 .…”
Section: Resultsmentioning
confidence: 80%
“…In the long past organochlorine pesticides (OCPs) like endrin were used in rice while other OCPs were used legally in other crops until 1977 when the last OC insecticide heptachlor was banned. The OCPs are lipophilic in nature, their hydrophobicity, low chemical and biological degradation rates have led to their widespread accumulation in food chain (John et al, 2001;Bedi et al, 2005;Aulakh et al, 2006). The exposure of OCPs in humans creates severe health hazards particularly breast cancer, testicular cancer, endocrine dysfunction, births defects, lower sperm count (Brody and Rudel, 2003;Ahmed et al, 1996;Garry et al, 2004;Soto et al, 1998).…”
Section: Introductionmentioning
confidence: 99%